1986
DOI: 10.1016/0304-3959(86)90026-6
|View full text |Cite
|
Sign up to set email alerts
|

A rating system for use with patient pain drawings

Abstract: Patients entering treatment for chronic benign pain often are asked to complete drawings indicating the intensity and location of their pain as part of the diagnostic process. While inferences have been made from pain drawings about the relative contributions of physiological and psychological factors to the patient's experience of pain, previous research has provided only equivocal support for this practice. A reliable method for assessing pain drawings is needed both for clinical use and to assess the validi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
276
0
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(280 citation statements)
references
References 12 publications
2
276
0
2
Order By: Relevance
“…The pain score method used in this study was a simplified version of those used by Margolis et al [22] and Parker et al [32], much like the simplified method suggested by Ohnmeiss et al [30]. Such scoring methods have been shown to have a very high reliability/repeatability [22,28,32], and furthermore offer the advantage that nonexperts can perform scoring, as it involves no clinical judgement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pain score method used in this study was a simplified version of those used by Margolis et al [22] and Parker et al [32], much like the simplified method suggested by Ohnmeiss et al [30]. Such scoring methods have been shown to have a very high reliability/repeatability [22,28,32], and furthermore offer the advantage that nonexperts can perform scoring, as it involves no clinical judgement.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic value of the pain drawing is most often based on whether the pain markings correspond with relevant anatomical structures or not [3, 29,30,33,39]. Also, for evaluation and quantification of pain, several surface-based methods have been applied [20,22,27,30].…”
Section: Pain 5 Years After Instrumented and Non-instrumented Posteromentioning
confidence: 99%
“…Body pain diagrams, which have been used for more than 20 years in musculoskeletal pain research, provide a rapid and inexpensive way to measure the extent, distribution, and location of pain [14,18,21,24,28]. Widespread pain has been recognized as a poor prognostic factor in diseases such as rheumatoid arthritis, cancer, and chronic low back pain, and a poor prognostic factor for outcome of TKA [18,28].…”
Section: Introductionmentioning
confidence: 99%
“…Widespread pain has been recognized as a poor prognostic factor in diseases such as rheumatoid arthritis, cancer, and chronic low back pain, and a poor prognostic factor for outcome of TKA [18,28].…”
Section: Introductionmentioning
confidence: 99%
“…Dermatome Pain Map: The Dermatome Pain Map (DPM) (5,6) includes two line drawings of the human body and is designed to assess anatomical pain location. Patients were asked to shade in the spatial distribution of their pain or discomfort.…”
Section: Instrumentsmentioning
confidence: 99%